Shifts in Maritime Trade Routes as a Result of Red Sea Shipping Crisis Detected in TROPOMI NO2 Data - A. Pseftogkas; T. Stavrakou; J.‐F. Müller; M.‐E. Koukouli; D. Balis; C. Meleti (Geophysical Research Letters, 2024)
Abstract Observations from space‐borne spectrometers have been lately used to quantify shipping emissions of nitrogen oxides (ΝΟΧ). Here we present a method that enhances the shipping signal of NO2 TROPOspheric MOnitoring Instrument (TROPOMI) satellite sensor observations in order to assess the impact of the Red Sea ship attacks on NO2 levels in three important shipping routes along the Red Sea, the Cape of Good Hope, and the Gibraltar Strait. Major shipping carriers, sailing usually via the Red Sea, have responded to the attacks by transiting their fleet around the African continent. The shipping signal from TROPOMI declines by ∼55% in the Red Sea and ∼15% in the Gibraltar Strait while an increase of ∼40% is found off the South African coast between January–June 2024 and the same period in 2023. These changes correlate well with vessel statistics, demonstrating the ability to track abrupt changes in NO2 shipping levels with satellite measurements.